Reverse factoring in the supply chain: objectives, antecedents and implementation barriers - Liebl, John; Hartmann, Evi; Feisel, Edda (International Journal of Physical Distribution & Logistics Management, 2016)
Purpose Reverse factoring (RF) can generate win-win situations for buyers, banks and suppliers. However, the supply chain management literature generally tends to ignore financial influences and accounting support structures. Research in the area of RF is relatively new and considerably fragmented. The purpose of this paper is to address this research gap and provide an analysis of the objectives, antecedents and barriers of implementation. Design/methodology/approach The study contributes fundamental new insights derived from 11 case studies. In total, 28 interviews were conducted from the perspective of buyers, banks and suppliers and analyzed regarding influencing factors of different RF approaches. Findings RF predominantly is used to extend days payable outstanding. However, secondary objectives such as the reduction of supplier default risk and process simplifications also play an important role. The number of integrated suppliers, dependence of suppliers on their buyers, spread between internal refinancing and RF costs and the diversity of target agreements strongly influence these objectives and therefore the configuration of RF solutions. Originality/value Most studies fall short of exploring the mechanism of RF from all of the different perspectives of buyers, banks and suppliers. This approach allows new insights regarding prerequisites and different motivations behind RF.
Keywords: Case; study; Supply; chain; finance; Reverse; factoring; Financial; supply; chain; management

Supply chain operations value – a new way of measuring cost-performance relations - Liebl, John; Hartmann, Evi; Feisel, Edda (DSI Annual Meeting 2016, 2016)

Trade credit, cost of capital and the role of buyer market power from an agency-theory perspective - Liebl, John; Plewa, Markus; Hartmann, Evi (DSI Annual Meeting 2016, 2016)